Single Molecule Analysis of Laser Localized Interstrand Crosslinks - Huang, Jing; Gali, Himabindu; Paramasivam, Manikandan; Muniandy, Parameswary; Gichimu, Julia; Bellani, Marina A.; Seidman, Michael M. (Frontiers in Genetics, 2016)
DNA interstrand crosslinks (ICLs) block unwinding of the double helix, and have always been regarded as major challenges to replication and transcription. Compounds that form these lesions are very toxic and are frequently used in cancer chemotherapy. We have developed two strategies, both based on immunofluorescence, for studying cellular responses to ICLs. The basis of each is psoralen, a photoactive (by long wave ultraviolet light, UVA) DNA crosslinking agent, to which we have linked an antigen tag. In the one approach, we have taken advantage of DNA fiber and immunoquantum dot technologies for visualizing the encounter of replication forks with ICLs induced by exposure to UVA lamps. In the other, psoralen ICLs are introduced into nuclei in live cells in regions of interest (ROI) defined by a UVA laser. The antigen tag can be displayed by conventional immunofluorescence, as can the recruitment and accumulation of DNA Damage Response (DDR) proteins to the laser localized ICLs. However, substantial difference between the technologies creates considerable uncertainty as to whether conclusions from one approach are applicable to those of the other. In this report we have employed the fiber/quantum dot methodology to determine lesion density and spacing on individual DNA molecules carrying laser localized ICLs. We have performed the same measurements on DNA fibers with ICLs induced by exposure of psoralen to UVA lamps. Remarkably, we find little difference in the adduct distribution on fibers prepared from cells exposed to the different treatment protocols.. Furthermore, there is considerable similarity in patterns of replication in the vicinity of the ICLs introduced by the two techniques